Disease profiles of sheep and goats in two groups of villages in southwest Nigeria - Adeoye, S.A.O. (International Livestock Centre for Africa, 1985)
Reports on 12-month observations on the animal health picture in West African Dwarf goats & sheep flocks in the villages of Badeku & Ipire in southwest Nigeria, detailing changes in morbidity & mortality following interventions to control peste des petits ruminants & sarcoptic mange, their major causes.